The influence of social media use on students' academic engagement and health outcomes - Akmal Ahmad Wafi; Purnamasari Purnamasari; Stella Putri Pradita; Berliana Julianti; Nur Kholipah (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2025)
The primary issue in this research is the impact of social media use, which can have both positive and negative influences on students. Social media provides real-time access to information and enables freedom of expression; however, it also presents risks such as privacy violations, cyberbullying, and mental health challenges. These concerns raise questions about the extent to which social media affects students' mental health and learning interest. This research aims to understand the impact of social media use on students' mental health. Social media, as a communication tool that has become part of everyday life, provides users with access to information from around the world in real-time. This can be utilized by students to find information related to their studies, thereby stimulating their interest in learning more effectively. Social media is known as a platform for expression, where individuals can freely express themselves online. However, social media can also be a double-edged sword for its users. Unlimited access to information can lead to risks such as privacy violations. The freedom to express oneself can also be exploited by certain individuals to harm others anonymously, causing mental distress or even depression for the victims. Abstrak. Permasalahan utama dalam penelitian ini adalah dampak penggunaan media sosial yang dapat memberikan pengaruh positif maupun negatif terhadap siswa. Media sosial menawarkan akses informasi real-time dan kebebasan berekspresi, namun juga menghadirkan risiko seperti pelanggaran privasi, cyberbullying, dan tekanan mental. Kondisi ini menimbulkan pertanyaan tentang sejauh mana media sosial memengaruhi kesehatan mental dan minat belajar siswa. Penelitian ini dilakukan dengan tujuan untuk mengetahui dampak penggunaan media sosial terhadap kesehatan mental siswa. Media sosial, sebagai perangkat komunikasi yang telah menjadi bagian dari kehidupan sehari hari dapat memberikan penggunanya akses terhadap informasi dari seluruh dunia secara real-time. Hal ini dapat dimanfaatkan oleh pelajar guna mencari informasi yang terkait dengan pembelajaran sehingga mampu merangsang minat belajar siswa secara lebih efektif.  Media sosial dikenal sebagai panggung berekspresi karena setiap individu dapat mengekspresikan dirinya dengan lebih bebas secara daring. Namun, media sosial juga dapat menjadi pedang bermata dua bagi penggunanya. Akses informasi tanpa batas dapat membahayakan hingga berujung pada pelanggaran privasi. Hak berekspresi yang bebas juga dapat dimanfaatkan oleh segelintir oknum untuk menjatuhkan individu lain secara anonim sehingga korbannya akan mengalami tekanan mental hingga depresi.